(untitled) (CAHIERS MAGELLANES-NS, 2024)
India is a multilingual land of more than 25 languages of its own. Additionally, there are several foreign languages taught here like German, Chinese, Italian etc., out of which French has a popular place. “French as a foreign language is learnt by more than 1,00,000 Indian students in Delhi alone”, stated the database of Institut Francais en Inde this year. Given the 25 years of Indo-French strategic partnership, we have multiple job openings within and outside the country for French learners. Hence, there is a constant increase in the number of students enrolling each year for French learning in India. So, it is imperative to delve into the specific problems that the students face to master the French language and to provide solutions to them. The paper wishes to deal with problems that arise when a Hindi speaker or a Punjabi speaker or any other regional language speaker, who lacks the knowledge of English, enrols for French classes. Secondly, it aims to explore the goals of Faculty Development Programs (FDPs) for teachers who teach French to regional language speakers given the fact that the FDPs by French native officials do not often meet the needs of the Indian FLE teachers. Thus, the paper aims to comprehend whether the FDPs render specific strategies and tools to French teachers for teaching French to regional language speakers who do not speak English.